Studi Efek Kontinuitas Pada Tekuk Torsi Lateral Balok Terlentur - Paulus Karta Wijaya (Universitas Katolik Parahyangan, 2011)
Steel beams with bending moment, have a kind of instability called lateral torsional buckling. The criticalmoment of a beam depends on its length, distribution of bending moment and on its end condition. Often,the beam is laterally supported on some points of the beam to increase critical moment. In AISCSpecification for Structural Steel Buildings takes the lengh as the unbraced length, which means thedistance between these lateral bracing. The AISC doesnot taken into account the influence of the parts ofthe beam which continuously connected to the part of the beam which is being considered. In thisresearch, the influence of the other parts of the beam is studied. Calculation of critical moment isperformed using finite difference method considering the beam as a whole, with its lateral support. Acomputer program is developed to performed the analysis. The results of this study is that the when thewhole beam is analysed, the critical moments is increased significantly compared to critical momet fromAISC method. For the beam being considered in this study, the increase is up to 49%. The conclusions ofthis study is that the analysis of critical moment for lateral torsional bukling, has to be performedconsidering all part of the beam.